Pengaruh Metode Pembelajaran Quiz Team berbantuan Media Baambozle terhadap Keaktifan dan Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VII MTsN 6 Tulungagung - Siti Nurlailil; Larasati Widoningtyas (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research was motivated by the relatively low level of student learning activities, indicated by limited participation in asking questions, answering, and expressing opinions during the learning process. In addition, some students showed low concentration and attention to the teacher’s explanations. The learning process was still teacher-centered, which reduced student activeness and affected learning outcomes. To address this problem, teachers need to apply learning methods that encourage student participation while improving learning outcomes. One method that can be applied, particularly in social studies subjects, is the Quiz Team learning method. This study aimed to determine the effect of the Quiz Team learning method assisted by Baambozle media on student activity and learning outcomes in social studies at MTsN 6 Tulungagung. The study used a quantitative approach with a quasi-experimental design, specifically a non-equivalent control group design. Data were collected through questionnaires, tests, and documentation. Questionnaires were used to measure student learning activity, while tests were used to assess learning outcomes. The sample consisted of 32 students in the control class and 32 students in the experimental class selected through purposive sampling. The results showed that the Quiz Team method assisted by Baambozle media significantly affected students’ activity and learning outcomes, indicated by a Sig. (2-tailed) value of 0.000 < 0.05. The findings imply that this method can enhance student activity and consequently improve learning outcomes.